2020
DOI: 10.2147/dddt.s232130
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cardioprotective Effect of Monoammonium Glycyrrhizinate Injection Against Myocardial Ischemic Injury in vivo and in vitro: Involvement of Inhibiting Oxidative Stress and Regulating Ca<sup>2+</sup> Homeostasis by L-Type Calcium Channels</p>

Abstract: Monoammonium glycyrrhizinate (MAG) is an aglycone of glycyrrhizin that is found in licorice and is often used clinically as an injection to treat liver diseases. However, the effect of MAG injection on cardiac function and its possible cellular mechanisms remain unclear. We explored the protective effects of MAG against myocardial ischemic injury (MII) induced by isoproterenol (ISO), as well as the cellular mechanisms via molecular biology techniques and patch-clamp recording. Methods: A rat model of myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Mitochondria injury was further validated with mitochondria oxidative stress marker SOD and MDA, and membrane damage indicator LDH in transfected A549 cells. 21,22 As expected, activity of SOD, MDA and LDH exhibited the same trend with JC-1 labeled flow cytometry (Figure 4B, *p<0.05 versus control, and # p<0.05 versus miR-199a-3p or pcDNA-ZEB1). Overexpression of miR-199a-3p decreased activity of SOD, and this was partly alleviated with co-transfection of ZEB1.…”
Section: Overexpression Of Mir-199a-3p Induced Mitochondria Injury Of A549supporting
confidence: 80%
“…Mitochondria injury was further validated with mitochondria oxidative stress marker SOD and MDA, and membrane damage indicator LDH in transfected A549 cells. 21,22 As expected, activity of SOD, MDA and LDH exhibited the same trend with JC-1 labeled flow cytometry (Figure 4B, *p<0.05 versus control, and # p<0.05 versus miR-199a-3p or pcDNA-ZEB1). Overexpression of miR-199a-3p decreased activity of SOD, and this was partly alleviated with co-transfection of ZEB1.…”
Section: Overexpression Of Mir-199a-3p Induced Mitochondria Injury Of A549supporting
confidence: 80%
“… 30 Zhao et al have demonstrated that monoammonium glycyrrhizinate, an aglycone of glycyrrhizin that can be extracted from liquorice, provides protection against ISO-induced MI damage (in vivo and in vitro). 31 Furthermore, we found that MgIG can reduce the concentration of intracellular calcium ions and the contractility of myocardial cells by inhibiting the L-type calcium current of myocardial cells, which has a similar effect to calcium antagonists. 32 However, to our knowledge, no study has explored the protection offered by MgIG in ATO-induced cardiotoxicity or the underlying mechanism.…”
Section: Introductionmentioning
confidence: 74%
“…Previous studies have reported that MgIG has strong myocardial protections, including anti-myocardial fibrosis, anti-myocardial ischemia (MI), and infarction. 30 , 31 Among them, Ma et al demonstrated that MgIG could reduce myocardial fibrosis in mice induced by isoproterenol (ISO), and the protective effects might be relevant to the decreased expression levels of NF-κB. 30 Zhao et al have demonstrated that monoammonium glycyrrhizinate, an aglycone of glycyrrhizin that can be extracted from liquorice, provides protection against ISO-induced MI damage (in vivo and in vitro).…”
Section: Introductionmentioning
confidence: 99%
“…However, Upadhyay and his colleagues suggested that the antioxidant property of licorice extract play a crucial role in the cardioprotective effect and preserving the cardiomyocytes health by licorice extract against doxorubicin-induced cardiotoxicity ( Upadhyay et al, 2020 ). The inhibiting of oxidative stress and regulating Ca 2+ homeostasis by L-Type Calcium Channels are responsible for the cardioprotective activity of monoammonium glycyrrhizinate injection against ISO-induced myocardial ischemia ( Zhao et al, 2020 ).…”
Section: The Potential Therapeutic Effect Of Glycyrrhizin and Licoricmentioning
confidence: 99%